Development of radish fibre based snack by response surface methodology (RSM) - Gupta, Prachi (Springer-Verlag, 2011)
This study aimed at optimization and development of radish fibre-rich snack using response surface methodology (RSM).The effect of ingredients on the quality of refined wheat flour (maida) based fried snack was studied. As the concentration of ghee in the formulation increased, the product became soft and lost its crispiness, thus affecting the overall acceptability. Radish fibre (5–20 g) was incorporated in the maida and the central composite design used to develop models for the responses. It was observed that ghee and fibre significantly (p ≤ 0.05) affected the acceptability and texture of fried product. Based on surface responses and 3D plots, level of fibre (20 g), maida (100 g) and ghee (15.12 g) were optimized to form a fibre-rich product, with high acceptability and better texture profile. The fibre-rich snack product contained nearly 8% more total dietary fibre (12.24%) than the control (4.25%). The product was stored for 6 months under ambient conditions during which it was stable and acceptable up to 4 months. At 5°C, it was stable up to 6 months in tri-laminated paper/Al-foil/polyethylene (PFP) pouches.